O povo Kaingang : arte e cultura - Catafesta, Simone Serpa (2013)
The contact of the Indians kaingang with white society in Rio Grande do Sul began in the late eighteenth century, with the developments in the medium and long term cultural exchange, leading the transformation of indigenous culture, with the incorporation of new elements and the loss of others. This research aims to studythe process of acculturation occurred between the Indians kaingang, noting the marks of these changes in his art and his craft, determining the traits that are kept, and how others have been adapted to meet the demands of indigenous communities and consumer market. It also seeks to investigate the transmission and actualization of values, knowledge and practicesfrom generation to generation, and more recently, in school, keeping alive the language, rituals and festivals, and living with new technologies. How spatial and temporal clipping, we chose Nonoai Indian Reservation, located between the cities of Laurel Lawn and Nonoai, upstate,in the period of a century (1913-2012). Justified the relevance of this approach for its thematic originality, and the very peculiarities of this Indian reservation, created in 1913, the focus of many conflicts and profound cultural changes. Methodologically, we performed a review of the literature pertinent to the subject, and the collection of empirical data, with a visit to the reserve and record oral information. The survey found that indigenous knowledge, here including art, crafts, language, customs and traditions are passed down from generation to generation in family life, in the spaces of sociability and in the school, keeping alive the tradition oral. Igualmente, the transformation or modernization that occurred in practice and in the making of art and craft, with the substitution of raw materials extracted from nature. The situation of the communities that are part of Indian territory in question has the most varied conditions, however, their social structure and cosmological principles remain in effect. The making of crafts and language are possibilities for dissemination of indigenous culture. In this perspective, we believe that the changes and transformations of this craft, including its modernization, is the result partly of acculturation and own demand.Therefore, the history of Indian culture kaingang allows usto reflect on the various possibilities of records effected by oral history. This reflection gives opportunity to know the day to day practices and the actions taken by this population.